Propensity for somatic expansion increases over the course of life in Huntington disease - Kacher, Radhia; Lejeune, François-Xavier; Noël, Sandrine; Cazeneuve, Cécile; Brice, Alexis; Humbert, Sandrine; Durr, Alexandra (eLife, 2021)
Recent work on Huntington disease (HD) suggests that somatic instability of CAG repeat tracts, which can expand into the hundreds in neurons, explains clinical outcomes better than the length of the inherited allele. Here, we measured somatic expansion in blood samples collected from the same 50 HD mutation carriers over a twenty-year period, along with post-mortem tissue from 15 adults and 7 fetal mutation carriers, to examine somatic expansions at different stages of life. Post-mortem brains, as previously reported, had the greatest expansions, but fetal cortex had virtually none. Somatic instability in blood increased with age, despite blood cells being short-lived compared to neurons, and was driven mostly by CAG repeat length, then by age at sampling and by interaction between these two variables. Expansion rates were higher in symptomatic subjects. These data lend support to a previously proposed computational model of somatic instability-driven disease.